Starting out with C++ early objects - Gaddis, Tony (Pearson/Addison Wesley, 2007)
Gaddis covers objects and classes early after functions and before arrays and pointers. As with all Gaddis texts, clear and easy-to-read code listings, concise and practical real-world examples, and an abundance of exercises appear in every chapter.